Elements of Geology - Lyell, Charles (Place of publication not identified : publisher not identified, 1838)
Between 1830 and 1833, Charles Lyell (1797-1875) published his three-volume Principles of Geology, which has also been reissued in this series. The work's renown stems partly from the fact that the young Charles Darwin, on his voyage around the world aboard the Beagle, became influenced by Lyell's ideas relating to gradual change across large spans of time. Shaping the development of scientific enquiry in Britain and beyond, Lyell was determined to disconnect geology from religion. He originally intended some of the present work, first published in 1838, to be a supplement to the Principles, but later expanded it to serve as a general introduction to geology. The topics covered include the formation of various rock types, matters of field geology, and how the presence of marine fossils above sea level could be explained by the land rising, rather than the sea retreating. Many salient points are illustrated with woodcuts.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).